A multicell structural battery composite laminate. Issue 3 (11th January 2022) - Xu, Johanna; Geng, Zeyang; Johansen, Marcus; Carlstedt, David; Duan, Shanghong; Thiringer, Torbjörn; Liu, Fang; Asp, Leif E.
Abstract: Multifunctional materials facilitate lightweight and slender structural solutions for numerous applications. In transportation, construction materials that can act as a battery, and store electrical energy, will contribute to realization of highly energy efficient vehicles and aircraft. Herein, a multicell structural battery composite laminate, with three state‐of‐the‐art structural battery composite cells connected in series is demonstrated. The experimental results show that the capacity of the structural battery composite cells is only moderately affected by tensile loading up to 0.36% strain. The multicell structural battery laminate is made embedding the three connected structural battery composite cells between carbon fiber/glass fiber composite face sheets. Electrochemical performance of the multicell structural battery is demonstrated experimentally. High charge transfer resistance for the pack as well as the individual cells is reported. Mechanical performance of the structural battery laminate is estimated by classical laminate theory. Computed engineering in‐plane moduli for the multicell structural battery laminate are on par with conventional glass fiber composite multiaxial laminates. Abstract : Structural batteries offer lightweight solutions for electrical systems. With these materials, energy efficiency can be improved across transport modes. Herein, multifunctional durability of structural battery composite cells is proven for alternating electrochemical and tensile mechanical loads. Furthermore, a multicell structural battery laminate operating at 10.5 V is manufactured and its multifunctional performance characterized, experimentally and theoretically.